Dietary Supplementation With Icariin Affects Estrogen Synthesis, Vitellogenesis, and Oocyte Development in the Chinese Mitten Crab, Eriocheir sinensis - Zheng, Xiaochuan; Liu, Wenbin; Liu, Jiadai; Zhang, Caiyan; Zhang, Ling; Gao, Fan; Zhang, Dingdong; Chi, Cheng (Frontiers in Marine Science, 2020)
In Eriocheir sinensis aquaculture, crabs feeding an artificial diet without steroid hormones available in ice-fresh fish or snails show delayed ovarian maturation and a delay in listing. Icariin (ICA), a safe monomer compound derived from plant, can effectively promote oestradiol (E2) synthesis and ovarian development in mammals, but its use on crustaceans has not been reported. We investigated the effects of ICA on oestrogen synthesis, vitellogenesis, and oocyte development in Chinese mitten crabs fed one of four diets containing 0, 50, 100, and 200 mg/kg ICA, respectively, for eight weeks. Results showed that vitellogenin contents, gonadosomatic indexes, and oocyte volumes in ICA50 and ICA 100 crabs were significantly higher than those in the control. The highest up-regulated expression of Vitellogenin (VTG) in hepatopancreases and ovaries were detected in ICA100 crabs. Haemolymph E2 contents were also significantly increased in ICA100 crabs. Enzyme-linked immunosorbent assay and western blot analysis indicated that the increase in E2 concentrations was attributable to an elevation in aromatase protein levels in ovaries through the cyclic adenosine monophosphate/ protein kinase A/ cAMP response element binding protein pathway. These findings suggest that ICA could serve as a natural additive to resolve the problem of delayed ovarian maturation of crabs raised in ponds.